Translation and validation of Malay version stroke knowledge test: extension study experience - Sowtali, Siti Noorkhairina (2018)
To translate and validate the Malay version of the Stroke Knowledge Test (SKT) research tool developed by Sullivan and Dunton (2004) among stroke patients.